Endocrine Prehabilitation - Sanjay Kalra; Gaurav Sachdeva; Nitin Kapoor (Journal of the Pakistan Medical Association, 2023)
We conceptualize and define endocrine and metabolic prehabilitation as enhancement of physical, psychosocial and social health, prior to a planned medical, surgical or radiotherapeutic endocrine/metabolic intervention, in order to ensure optimal therapeutic outcomes during and after the procedure. This is similar to, but different from the process of endocrine rehabilitation, which follows endocrine therapy. All health care professionals, working as a team, should take responsibility of endocrine prehabilitation. Keywords: Endocrinology, metabolism, pre-operative control, team-based care.